Foodscape: A scoping review and a research agenda for food security-related studies. - Simon Vonthron; Coline Perrin; Christophe-Toussaint Soulard (PLoS ONE)
Since 1995, the term 'foodscape', a contraction of food and landscape, has been used in various research addressing social and spatial disparities in public health and food systems. This article presents a scoping review of the literature examining how this term is employed and framed. We searched publications using the term foodscape in the Web of Science Core Collection, MEDLINE, and Scopus databases. Analyzing 140 publications, we highlight four approaches to the foodscape: (i) Spatial approaches use statistics and spatial analysis to characterize the diversity of urban foodscapes and their impacts on diet and health, at city or neighborhood scales. (ii) Social and cultural approaches at the same scales show that foodscapes are socially shaped and highlight structural inequalities by combining qualitative case studies and quantitative surveys of food procurement practices. (iii) Behavioral approaches generally focus on indoor micro-scales, showing how consumer perceptions of foodscapes explain and determine food behaviors and food education. (iv) Systemic approaches contest the global corporate food regime and promote local, ethical, and sustainable food networks. Thus, although spatial analysis was the first approach to foodscapes, sociocultural, behavioral and systemic approaches are becoming more common. In the spatial approach, the term 'foodscape' is synonymous with 'food environment'. In the three other approaches, 'foodscape' and 'food environment' are not synonymous. Scholars consider that the foodscape is not an environment external to individuals but a landscape including, perceived, and socially shaped by individuals and policies. They share a systemic way of thinking, considering culture and experience of food as key to improving our understanding of how food systems affect people. Foodscape studies principally address three issues: public health, social justice, and sustainability. The review concludes with a research agenda, arguing that people-based and place-based approaches need to be combined to tackle the complexity of the food-people-territory nexus.